Comprehensive selection and assessment methodology of compression heat pump system. (15th February 2022) - Jiang, Jiatong; Hu, Bin; Ge, Tianshu; Wang, R.Z.
Abstract: In the process of "Carbon peaking" and "Carbon neutrality", compression heat pump is an effective technology to supply heat while improving energy utilization efficiency and shifting CO2 emission. In order to promote the application of compression heat pump and provide the most suitable heat pump system, the favorable design logic and selection strategy is important for researchers and designers. Therefore, a comprehensive selection and assessment system (S&A) of compression heat pump is proposed in this article. Taking waste heat temperature, required supply temperature, heating capacity, energy efficiency as input parameters, the system first classifies heat pump according supply temperature to select refrigerants, followed by choosing compressor and heat exchanger types based on heating capacity, and last selects configuration by efficiency requirement. All the satisfied combinations of refrigerant, compressor, heat exchanger, system configuration can be output, also the optimal combination based on the highest coefficient of performance (COP). Further, the selected heat pump systems will be assessed from economic and environmental aspects. Two case studies are carried on to show the selecting and simulating process for low-temperature and high-temperature heat pump, and to prove the reliability of compression heat pump S&A system. Highlights: A comprehensive selection and assessment methodology of compression heat pump is proposed. Energy efficiency, economic and environment assessment are all included in the methodology. The selection process includes refrigerants, compressor, heat exchanger and configuration. Two case studies are shown, highlighting successful demonstration of the system.